The healing power of stinging nettle: unlocking the medicinal properties of a versatile herb / Dr. Mohd Izani Othman - Othman, Mohd Izani (Universiti Teknologi MARA, Negeri Sembilan, 2023)
Nettle, also known as stinging nettle (Urtica dioica) has been used for medicinal purposes for thousands of years, with its use dating back to ancient civilizations including the Greeks and Romans. In Malaysia, this herb is known as “Jelatang” and is traditionally used as a general tonic to improve overall health and treat a wide range of health conditions. In the Middle Ages, stinging nettle was used to treat gout, a painful condition caused by the build-up of uric acid in the joints. In the 19th century, stinging nettle was used as a remedy for rheumatism, diabetes, and digestive problems. Today, numerous traditional applications of this herb have been confirmed by modern research, and its medicinal properties are widely acknowledged. Stinging nettle is commonly used as a natural remedy for allergies, arthritis, and prostate problems.